(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The Institutional provision of gas transportation enterprises activity was investigated in the article. The organizational and economic basis of functioning of gas transport enterprises is Outlined. A review of theoretical approaches to understanding "gas transportation enterprise" and by systematization given a unified definition of the concept is Carried out. The functioning normative provision of the gas transportation sphere existence is Traced. The organizational and economic basis of providing the activity of gas transport enterprises is proposed, the following organizational and economic ways of efficiency of gas transport enterprises activity are offered. A Key tool for management entities in the conditions of managed and sustainable development is to develop separate processes of interaction between institutional subjects. Among the considerable number of instruments should be selected: economic, economic, market, social, managerial, organizational and economic, etc. The nitrogen transport enterprises are one of the elements of strategically important gas transportation industry, forming the impact of social and economic character on the life level and energy dependence. Consumers for today, forming market demand, require the gas transport enterprise of high quality services, the main parameters of which is the continuity, reliability, chemical-physical characteristics, optimal technological indicators, etc. However, it is necessary to note that these areas are not sufficiently justified today, and therefore in Ukraine there is no necessary institutional provision to implement these organizational transformations. As for the form of ownership, its choice is due To a significant number of factors, so all decisions on its change for the objects of the gas transportation system should be sufficiently grounded, and thus the possible variant of development is a combination of several different forms. It is Worth noting that for the enterprises of the gas transportation system of Ukraine, which are natural monopolies, there are no competitors in the spheres of establishment of standards and improvement of activity, so they, despite the form of ownership, are considerably limited in Responsibility to consumers. So, first of all, it is important to deprive Functioning of the gas transport system and harmonization of relations between the State, gas transport enterprises and consumers is possible due to introduction of effective organizational and investment regulation of their activity. In Particular, the main provisions would have to be focused on the. Thus, the conclusion is that the most important factor of influence on the efficiency of enterprises of gas transportation sphere is institutional system of interaction of all institutions, which forms the necessary institutional environment with the existing harmonious relations between its Elements.